The Analysis of Algebraic Problem Solving Ability on Students of Package B Equivalency - Ovan, Ovan; Nasruddin, Nasruddin; Tasni, Nurfaida; Chairuddin, Chairuddin; Saputra, Andika (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2023)
This study aims to analyze the algebraic problem-solving abilities of student package B equivalence. Data collection was conducted on students of package B equivalency at the Community Learning Activity Center (PKBM) of Rahmatan Lil-Alamin Makassar, South Sulawesi. The method used in this research is quantitative. The results of the study showed that 45% of students who completed, while students who did not complete were 55%, meaning that there were more students who did not complete than completed. Students' classical completeness also gets a percentage of 40%, it means that students do not complete classically. The students have not been able to understand algebraic problem and students experience concept errors and problem solving procedures. Students must be trained to do algebraic questions more routinely and students are also given algebraic questions related to the context of students' daily life. The research is needed to be done further on other variables such as conceptual understanding, problem solving errors, as well as material to be tested such as geometry, arithmetic, and statistics.